2021
DOI: 10.3390/nano11020395
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanofiber Composite with Bimetallic Zeolite Imidazole Framework for Electrochemical Supercapacitors

Abstract: Cellulose nanofiber (CNF) and hybrid zeolite imidazole framework (HZ) are an emerging biomaterial and a porous carbonous material, respectively. The composite of these two materials could have versatile physiochemical characteristics. A cellulose nanofiber and cobalt-containing zeolite framework-based composite was prepared using an in-situ and eco-friendly chemical method followed by pyrolysis. The composite was comprised of cobalt nanoparticles decorated on highly graphitized N-doped nanoporous carbons (NPC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…This nanostructure shows that G causes the Cu-MOFs nanostructure to transform from the original octahedral to hierarchical flower-like nanostructures. A similar phenomenon was observed by Yadav et al [21] after the incorporation of cellulose nanofibers (CNF) into MOFs. CNF and hybrid zeolite imidazole framework (HZ) was developed from biomaterial and porous carbon-based material, respectively.…”
Section: Solvothermal Synthesis Methodssupporting
confidence: 79%
“…This nanostructure shows that G causes the Cu-MOFs nanostructure to transform from the original octahedral to hierarchical flower-like nanostructures. A similar phenomenon was observed by Yadav et al [21] after the incorporation of cellulose nanofibers (CNF) into MOFs. CNF and hybrid zeolite imidazole framework (HZ) was developed from biomaterial and porous carbon-based material, respectively.…”
Section: Solvothermal Synthesis Methodssupporting
confidence: 79%
“…A newly reported study from Yadav et al produced a composite of cellulose nanofibers and MOF-derived carbon, which is hybrid zeolite imidazole framework nanoporous carbon. [137] The electrodes made of this composite resulted in 146 F g −1 capacitance and had the ability to retain the capacitance at 90% after 2000 cycles; in which the values are promising for use in a supercapacitor. Thus, this study revealed a simple, promising supercapacitor electrode synthesis method.…”
Section: Nanocellulose/metal-organic Frameworkmentioning
confidence: 94%
“…Supercapacitors (SCs) can store energy via redox reaction or the formation of electric double layers (EDLs) of ionic species over the surface of electrodes at the electrode/electrolytes interface. They can reach the global requirements for ESS due to rapid power output, fast charge–discharge ability and longer lifetime than batteries [ 4 , 120 , 121 , 122 , 123 ]. SCs can be independently used as an alternative renewable energy source in the place of batteries in many fields such as wearable electronics, electric buses, laptops, mobiles, aerospace and various diagnostic instruments in medical systems, which boosts the growing interests in the field of advanced SCs research.…”
Section: Ionic Liquids (Ils) For Supercapacitors (Scs)mentioning
confidence: 99%